A note on the pricing of Australian government asset sales. (August 2014) - Docherty, Paul; Easton, Steve
Unlike acquiring company shareholders in Australian takeovers, but like shareholders in government initial public offerings, shareholders of companies purchasing Australian government assets earn economically and statistically significant positive abnormal returns. However, unlike privatisations via initial public offerings where all citizens are entitled to subscribe for shares, in privatisations via asset sales only acquiring company shareholders benefit from any under-pricing. This suggests the need for greater scrutiny to ensure fair pricing in privatisation via asset sales.